The Construction of Customary Values as Part of The Agreements’s Validity: Konstruksi Nilai Adat Sebagai Bagian Dari Keabsahan Perjanjian - Bagenda, Christina; Carbonilla, Cicilia Helena (Rechtsidee, 2022)
Agreement is one of the important aspects in civil law. This is because the agreement is one of the legal actions that are often and commonly carried out in everyday life. Article 1320 of the Civil Code actually confirms the conditions for the validity of the agreement, such as: competent, agree, certain things, are allowed by law. However, in practice, something that is permitted by law is not only interpreted as permitted by positive or written law. However, it also includes unwritten legal values in society, which in this case includes Customary Values. This study aims to verify the legal terms of the agreement, including the inclusion of customary values as a valid condition of the agreement. This research is a normative legal research with a conceptual approach and legislation. The novelty in this research is the effort to extend the legal terms of the agreement, especially the halal cause or things that are permitted by law, including those permitted by unwritten law, in this case the customary values that apply in society. The results of this study confirm that with a futuristic and extensive interpretation, the meaning of halal causes or things permitted by law as a condition for the validity of the agreement must be expanded so that it includes unwritten law including customary values. Customary values that are still alive and valid in society are categorized as living law so that they become unwritten law. Because it is still valid in the community, customary values as unwritten law must be considered rights in making an agreement. This confirms that local customary values as long as they are still valid and live in the community can be a parameter as a condition for the validity of the agreement through the expansion of halal causes or something permitted by law in Article 1320 of the Civil Code.